Fractal method of forming etalon images in vision systems - Yuzefovich, V. V.; Butochnov, A. N.; Mezentsev, A. V.; Mironyuk, S. V. (Інститут проблем реєстрації інформації НАН України, 2015)
Based on the analysis of existing methods of image processing in vision systems, there is proposed to use a fractal method for forming etalon images as the most appropriate by criterion of computational feasibility. Fig.: 5. Refs: 10 titles.